Effect of L-dopa alone and with benserazide on the spontaneous activity of striatal neurones in normal and 6-hydroxydopamine-lesioned rats - Chang, W Y (1997)
1. The effects of L-dopa methylester (LDME), an analogue of levodopa, on the spontaneous activity of dopamine sensitive neurones in the rat striatum, after 6-hydroxydopamine induced degeneration of the nigrostriatal tract were compared with those in unlesioned animals both in the absence and presence of benserazide, a peripheral DOPA decarboxylase inhibitor (PDI). 2. Studies were performed at 5–7 days post lesion (group 1 animals), at 21 days (group 2) when denervation supersensitivity was evident by contralateral turning to apomorphine and at the same time but following 7 days dosing with LDME plus benserazide (group 3). 3. In unlesioned animals, LDME alone inhibited spontaneous firing by some 45% over 60 min including a marked but transient early phase which was still present in all lesioned animals even though the later inhibition was significantly reduced in group 1 and 3 animals. 4. When given after benserazide in unlesioned animals LDME still produced a similar level of overall inhibition but without the early phase. The lesion reduced the overall inhibition, except in group 2 animals, and after chronic dosing (group 3) it was almost absent. 5. It is proposed that since the early inhibition with LDME alone is still seen after lesion of the nigrostriatal tract but not after the PDI benserazide, it is caused by peripherally formed dopamine and that as the delayed inhibition with LDME alone and after benserazide are all reduced by nigrostriatal lesions, as is its amphetamine like ipsilateral turning, that this depends on locally (striatal) synthesized dopamine. 6. This study also shows that chronic levodopa/PDI treatment reduces the compensating increased activity of surviving dopaminergic neurones and the functional supersensitivity to dopamine suggests that the long term administration of levodopa may reduce its own utilization and activity in the striatum and in the treatment of Parkinson's Disease.